2012
DOI: 10.3109/03639045.2012.683875
|View full text |Cite
|
Sign up to set email alerts
|

Development of self-microemulsifying drug delivery system for oral bioavailability enhancement of berberine hydrochloride

Abstract: The purpose of this study was to develop a self-microemulsifying drug delivery system (SMEDDS) to improve the oral bioavailability of Berberine hydrochloride (BBH), an important bioactive compound from Chinese Medicines with poor water solubility. Pseudoternary phase diagrams were constructed using oil, surfactant and co-surfactant types to identify the efficient self-microemulsification region. SMEDDS was characterized by morphological observation, droplet size, zeta-potential determination, stability, in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 35 publications
3
36
0
Order By: Relevance
“…These ions minimize the surface charge of nanoemulsions generated from self-emulsifying systems. 18 This is the reason that SGF shielded the negative charge of SNEDDS. The zeta potential of near 0 results in insufficient repulsion between droplets and subsequent aggregation, confirming the larger droplets in SGF as compared with water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These ions minimize the surface charge of nanoemulsions generated from self-emulsifying systems. 18 This is the reason that SGF shielded the negative charge of SNEDDS. The zeta potential of near 0 results in insufficient repulsion between droplets and subsequent aggregation, confirming the larger droplets in SGF as compared with water.…”
Section: Discussionmentioning
confidence: 99%
“…The complete solubilization by PEG 400 and SNEDDS suggested that the mechanism for the improvement in bioavailability brought about by the nanocarriers involved not only the dissolution rate. PEG 400 has strongly hydrophilic characteristics, 18 leading to difficulty with regard to partitioning into the lipophilic GI membrane. When dissolved in oil droplets, the drug can be absorbed directly by the membrane via fusion or interaction.…”
mentioning
confidence: 99%
“…Most of the articles on SMEDDS or SNEDDS highlighted the nano-scale dispersion as one of the major contributing factors behind improved drug absorption after oral administration compared to either normal solution or suspension (Zhu et al, 2013;. However, comparative in vivo studies with variable droplet size with the same SEDDS have been rarely reported.…”
Section: Importance Of Emulsion Droplet Size On Drug Absorptionmentioning
confidence: 99%
“…The retention time of Brb was ~7 minutes, and the encapsulation efficiency (EE%) of Brb in the Mic samples was calculated based on standard curves constructed in the range of 4-200 μg/mL (r 2 =0.998, n=3), which were validated for linearity, precision, and accuracy. 7,8,16 Physical stability of Brb-micelles…”
Section: Physicochemical Characterization Of Micelles Particle Size Amentioning
confidence: 99%
“…[2][3][4]9,12,18,21 Recently, several nanoparticulate delivery systems for Brb have been reported, attempting to address the major pharmaceutical concerns associated with its systemic administration, with lipid-based nanocarriers being the most investigated. 1,[6][7][8]12,16 Currently, lipopolymeric micelles are popular pharmaceutical delivery vehicles for poorly water-soluble active compounds, such as Brb, which can be solubilized within the hydrophobic core of a micelle. Micelles prepared from conjugates of polyethylene glycol (PEG) and diacyllipids, such as phosphatidylethanolamine (PE) -ie, PEG-PE conjugates -have demonstrated several pharmaceutical advantages such as small size (10-100 nm), good solubilization efficacy, low toxicity, controlled drug release, and extremely high stability due to very low critical micelles concentration (CMC) (typically in the micromolar range).…”
mentioning
confidence: 99%